1989
DOI: 10.1177/0148607189013002124
|View full text |Cite
|
Sign up to set email alerts
|

Resting Energy Expenditure in Patients with Alcoholic Hepatitis

Abstract: Patients with alcoholic hepatitis are typically malnourished. A hypermetabolic state would explain, at least in part, the muscle wasting observed in these patients. However, data on hypermetabolism in liver disease are limited and conflicting. In this study, we evaluated measured energy expenditure (MEE) vs predicted energy expenditure (PEE), and MEE in relation to urinary creatinine excretion in 20 patients with moderate and severe alcoholic hepatitis, and 20 controls. Patients with alcoholic hepatitis had de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…24 However, underestimates of mean measured REE have been recorded in this patient group using these formulae with individual differences between predicted and measured values exceeding 20% in one third of patients. 17,18,[25][26][27][28][29][30][31][32][33] No information is, however, available on the relative accuracy of the predictions in various population subgroups. Similarly, little if any information is available on the accuracy of the estimates of REE obtained, in this patient population, using other prediction formulae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 However, underestimates of mean measured REE have been recorded in this patient group using these formulae with individual differences between predicted and measured values exceeding 20% in one third of patients. 17,18,[25][26][27][28][29][30][31][32][33] No information is, however, available on the relative accuracy of the predictions in various population subgroups. Similarly, little if any information is available on the accuracy of the estimates of REE obtained, in this patient population, using other prediction formulae.…”
Section: Discussionmentioning
confidence: 99%
“…They suggest, but do not advocate, that if the facilities for measurement are not available, then energy expenditure could be estimated by use of the Harris-Benedict prediction formulae. 24 However, it has been shown that these formulae may underestimate mean measured values of REE in patients with cirrhosis by up to 13%, 17,18,[25][26][27][28][29][30][31][32][33] though presently, it is unclear whether this discrepancy is equally evident in all population subgroups.A number of alternative prediction formulae are available, 34-39 but the accuracy of the REE estimates derived from these has not been studied systematically in patients with chronic liver disease. A prediction formula developed specifically for use in this patient population, which incorporated a measure of fat-free mass (FFM) derived using bioelectrical impedance analysis, has been proposed by Mü ller et al 40 but this has not been validated.…”
mentioning
confidence: 99%
“…We found eight studies among the guidelines assessing REE in groups of malnourished or at-risk medical inpatients with various acute illnesses (acute renal failure [26], cancer [27,28], ulcerative colitis [29], acute pancreatitis [30], alcoholic hepatitis [31,32], congestive heart failure [33]). Among them, we found six studies (four observational studies [27À30] and two non-randomized trials [31,32]), in which REE was measured by indirect calorimetry and compared to the value predicted by Harris-Benedict formula.…”
Section: Indicationmentioning
confidence: 99%
“…Among them, we found six studies (four observational studies [27À30] and two non-randomized trials [31,32]), in which REE was measured by indirect calorimetry and compared to the value predicted by Harris-Benedict formula. The formula failed to accurately predict REE in all studies.…”
Section: Indicationmentioning
confidence: 99%
“…The nutritional and metabolic consequences of cirrhosis have attracted considerable interest over the past decade (1)(2)(3)(4)(5); given the central role of the liver in metabolism, it is not surprising that undernutrition is common in chronic liver disease (6)(7)(8). In recent years, the focus of research in this area has been on the identification of clinical or biochemical markers associated with nutritional risk (9,10).…”
Section: Introductionmentioning
confidence: 99%